Characterization Of Pectin As Biopolymeric Flocculant And Its Effectiveness In The Treatment Of Turbid Waste Water - Ho, Yeek Chia (2000)

(untitled)
Coagulation and flocculation processes were applied in the treatment of turbid wastewater. Two coagulants, namely, Al3+ and Fe3+ and three flocculants, namely, commercial pectin, industrial flocculant and self-extract pectin from orange peel were used to compare the effectiveness of the treatments. Response Surface Methodology for two responses, namely, flocculating activity and turbidity reduction was applied for the optimization of the treatment conditions. The physicochemical characteristics of the three flocculants were analyzed.